2009
DOI: 10.4103/0256-4947.55163
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in the growth of Saudi children and adolescents

Abstract: BACKGROUND AND OBJECTIVES:No previous study has provided a detailed description of regional variations of growth within the various regions of Saudi Arabia. Thus, we sought to demonstrate differences in growth of children and adolescents in different regions.SUBJECTS AND METHODS:The 2005 Saudi reference was based on a cross-sectional representative sample of the Saudi population of healthy children and adolescents from birth to 18 years of age. Body measurements of the length, stature, weight, head circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“… 26 Therefore, using the Saudi charts could reveal a higher percentage of obesity, which is one of the messages of this paper. 27 , 28 It is now widely thought that to achieve an effective functioning cardiorespiratory system, a minimum of moderate and vigorous activity carried out once weekly is required. A previous study 29 showed that most Saudi adolescents do not meet these requirements.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Therefore, using the Saudi charts could reveal a higher percentage of obesity, which is one of the messages of this paper. 27 , 28 It is now widely thought that to achieve an effective functioning cardiorespiratory system, a minimum of moderate and vigorous activity carried out once weekly is required. A previous study 29 showed that most Saudi adolescents do not meet these requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known regional variation in growth between regions in the Kingdom,[16] suggested variation in the prevalence of nutritional disorders including overweight and obesity. The objective of this report is to explore and assess the significance of regional variation in the prevalence of overweight and obesity in this population.…”
mentioning
confidence: 99%
“…These can be grouped as environmental, genetic, socioeconomic, nutritional and demographic factors (16). Altitude- and microclimate-related differences have also been reported to influence growth (14,17). However, nutrition and socioeconomic status are probably the dominant factors influencing growth in the first year of life (16).…”
Section: Discussionmentioning
confidence: 99%